Applying systematic review methods to studies of people's views: an example from public health research. Issue 9 (13th August 2004) - Harden, Angela; Garcia, Jo; Oliver, Sandy; Rees, Rebecca; Shepherd, Jonathan; Brunton, Ginny; Oakley, Ann
Abstract : Methods for systematic reviews are well developed for trials, but not for non-experimental or qualitative research. This paper describes the methods developed for reviewing research on people's perspectives and experiences ("views" studies) alongside trials within a series of reviews on young people's mental health, physical activity, and healthy eating. Reports of views studies were difficult to locate; could not easily be classified as "qualitative" or "quantitative"; and often failed to meet seven basic methodological reporting standards used in a newly developed quality assessment tool. Synthesising views studies required the adaptation of qualitative analysis techniques. The benefits of bringing together views studies in a systematic way included gaining a greater breadth of perspectives and a deeper understanding of public health issues from the point of view of those targeted by interventions. A systematic approach also aided reflection on study methods that may distort, misrepresent, or fail to pick up people's views. This methodology is likely to create greater opportunities for people's own perspectives and experiences to inform policies to promote their health.